The Effect Of Perineal Massage On The Degree Of Perineal Laceration In Primigravida Mother - Putu Andyna Natami (Coping: Community of Publishing in Nursing, 2013)
Maternal Mortality is still high indicates that the reproductive health of the mother is still cause for concern. Maternal mortality is the main Triassic bleeding. Postpartum hemorrhage is bleeding in excess of 500cc-600cc in the first 24 hours after the first child born resulting from the birth canal laceration. The birth canal can tear the vagina, cervix, uterus and perineum. Perineal laceration is a tear that occurs in the perineum during childbirth. Perineal laceration can result in pelvic muscle dysfunction basis, resulting in lower quality of life of the mother after giving birth. This causes the mother is not able to control bladder and bowel movements because there are some nerves or muscles are impaired. When this has been done while pregnant alternative methods aimed at minimizing perineal laceration, one of which is perineum massage. This study aims to determine the effect of perineal massage on the degree of perineal laceration in primigravida mother. Types of studies that used pre-experimental comparison group design with static. Sample consisted of 20 respondents, the sample was divided into two groups primigravida mothers who do perineum massage (10 respondents) and the primigravida mother who does not do perineal massage (10 respondents). Sampling technique used in this study is the technique of quota sampling. Data collection by observation of the degree of perineal laceration using the observation sheet. The results are given in groups of perineal massage, none having third and fourth-degree tear. Most respondents did not experience perineal laceration of six people (60%), three (30%) had torn one and one degree (10%) had a two-degree tear whereas those respondents who were not given the number of respondents perineal massage for 10 people. Most respondents experienced perineal tear degree two which is about 7 people (70%), the degree of a total of 2 people (20%) and did not experience as much as a man torn perineum (10%) and none having third and fourth-degree tear. Mann-Whitney test results seen the value of p = 0.005 or p <? (0.05), then the conclusion H0 is rejected, then there is the influence of perineal massage on the degree of perineal laceration in primigravida mother. In this regard it is suggested to optimize the health workers can be counseled about how to prevent perineal tears in labor and guide her to perform perineal massage.